STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER AGAMA DI MI MUHAMMADIYAH 1 BUTUH - El Syam, Robingun Suyud; Winarti, Mukti (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
This study is to elaborate on the learning strategies of Islamic religious education in the formation of religious character at MI Muhammadiyah 1 Butuh. This paper is the result of qualitative field research using questionnaires, interviews, documentation, and observation as data collection techniques, then analyzed and conclusions are drawn. The subjects of this study were Islamic Religious Education teachers at MI Muhammadiyah 1 Butuh, and the object was the Islamic Religious Education learning strategy in the formation of religious character. Based on previous findings and analysis, it can be concluded that positive values were consistently found in the implementation of Islamic Religious Education teaching, indicating the success of the learning technique, although there are still reports regarding the use of inadequate educational media. Religious programs are well managed and implemented including daily activities, weekly activities, monthly activities, and annual activity programs. After reviewing each table of findings, it can be said that the Islamic Religious Education Learning strategy is quite ideal because the percentage of implementation results is greater than 43%. This finding confirms the importance of the Islamic Religious Education learning strategy in developing students' religious character.